Single and double K-shell vacancy production in slow Xe54+,53+-Xe collisions - Hillenbrand, Pierre-Michel; Hagmann, S.; Kozhedub, Y. S.; Benis, E. P.; Brandau, C.; Chen, R. J.; Dmytriiev, D.; Forstner, O.; Glorius, J.; Grisenti, R. E.; Gumberidze, A.; Lestinsky, M.; et al. (Physical review, 2022)
We present an experimental and theoretical study of symmetric Xe54++Xe collisions at 50, 30, and 15 MeV/u, corresponding to strong perturbations with vK/vp=1.20, 1.55, and 2.20, respectively (vK is the classical K-shell orbital velocity and vp is the projectile velocity), as well as Xe53++Xe collisions at 15 MeV/u. For each of these systems, x-ray spectra are measured under a forward angle of 35∘ with respect to the projectile beam. Target satellite and hypersatellite radiation Kαs2,1 and Kαhs2,1, respectively, are analyzed and used to derive cross-section ratios for double-to-single target K-shell vacancy production. We compare our experimental results to relativistic time-dependent two-center calculations.